2004
DOI: 10.1111/j.1365-3040.2004.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of inorganic carbon in the edible cyanobacterium Ge‐Xian‐Mi (Nostoc) and its role in alleviating photo‐inhibition

Abstract: The present work investigated the inorganic carbon (C i ) uptake, fluorescence quenching and photo-inhibition of the edible cyanobacterium Ge-Xian-Mi ( Nostoc ) to obtain an insight into the role of CO 2 concentrating mechanism (CCM) operation in alleviating photo-inhibition. Ge-XianMi used HCO 3 -in addition to CO 2 for its photosynthesis and oxygen evolution was greater than the theoretical rates of CO 2 production derived from uncatalysed dehydration of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 64 publications
0
22
1
Order By: Relevance
“…Lower NPQ might also be attributed to the down-regulation of CCM which functions to concentrate intracellular CO 2 and subsequently acidify the thylakoid lumen (Raven, 1997). However, operation of the CCM can play a role in draining the electrons and lead to reduced photoinhibition (Qiu and Liu, 2004). The down-regulated CCM of P. tricornutum grown at high CO 2 could be associated with weakened cyclic electron transport (Moroney and Somanchi, 1999) that can also lead to higher photo-inhibition (Takahashi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Lower NPQ might also be attributed to the down-regulation of CCM which functions to concentrate intracellular CO 2 and subsequently acidify the thylakoid lumen (Raven, 1997). However, operation of the CCM can play a role in draining the electrons and lead to reduced photoinhibition (Qiu and Liu, 2004). The down-regulated CCM of P. tricornutum grown at high CO 2 could be associated with weakened cyclic electron transport (Moroney and Somanchi, 1999) that can also lead to higher photo-inhibition (Takahashi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that M. aeruginosa cells exposed to long-term UV-B radiation show a lower K ½ CO 2 compared to untreated samples (Song & Qiu, 2007). Other studies have examined the CCM of cyanobacteria under LC i , and it has been proposed that the CCM makes cyanobacteria more competitive during bloom formation (Qiu & Liu, 2004;Riding, 2006;Cheng et al, 2008); as yet, however, there is no experimental evidence for this.…”
Section: Introductionmentioning
confidence: 81%
“…Under LC i conditions, cyanobacteria show greater expression of their CCM-related components (Omata et al, 1999;Price et al, 2008). Qiu & Liu (2004) demonstrated that the operation of the CCM in cyanobacterium Nostoc served as a means of diminishing photodynamic damage by dissipating excess light energy. Furthermore, it has been found that high DIC constrains high light acclimation of the cyanobacterium Synechococcus (Burns et al, 2006).…”
mentioning
confidence: 99%
“…Two direct HCO3 2 uptake systems are proposed in cyanobacteria (Kaplan and Reinhold, 1999;Giordano et al, 2005): an ATP-binding cassette-type transporter with a high affinity for HCO3 2 (Bonfil et al, 1998;Ohkawa et al, 1998;Omata et al, 1999) and a Na 1 -dependent transporter (Miller et al, 1984;Kandasamy, 1992, 1994;Gao and Zou, 2001;Qiu and Liu, 2004). Many eukaryotic photosynthetic organisms, both freshwater and marine, are capable of direct utilization of HCO3 2 from the medium (Rotatore et al, 1995;Amoroso et al, 1998;Matsuda et al, 2001;Colman et al, 2002).…”
Section: Indirect Hco3mentioning
confidence: 99%